(untitled) (Gestão & Regionalidade, 2015)
The objective of this study is to analyze if there was convergence of income in the state of Paraná, Brazil, a period from 1995 to 2009. For this, we calculated the ? and ?-convergence. The ?-convergence was analyzed under three optical (absolute convergence, conditional and club), all estimated by panel data. The results showed a tendency of reducing inequalities in relation to economic growth throughout the state. Moreover, further analysis showed that not only was a trend of general convergence, but clearly identified a convergence between regions belonging to the same group, regions with identical rates of investment in physical capital, human and population.